LOS NUEVOS DESAFÍOS DE LA SOCIOLOGÍA - Tobón, Alonso (La Sociología en sus Escenarios, 2010)
Abstract. Professor Alonso Tobón comments in his paper "The present challenges of the Sociology", the balance presented by professor Alba Lucia Serna about Sociology in Medellin and the commentaries of professors Maria Teresa Uribe, Javier Galeano, Edgar Ramirez and Juan Maria Ramirez, who aim at a diagnosis of crisis in sociology and at a reserved prognosis, considering the lack of perspective, the absence of dialogue and the lack of academic communities. It raises that if we want to accept the challenge to make advance Sociology it is necessary to return to scientific Sociology. It argues that the increase of the students is positive, and the high supply of withdrawn; sample that the situation is optimistic. Tobón raises four challenges of present Sociology: It recommends the academic creation of forms of associations, institutions or schools that monopolize the knowledge and the professional performance. The Profession, occupation, use sociology struggles therefore in being a profession or an occupation. The refuge for the profession has been the university teaching, Science or humanities: qualitative or quantitative methods. The vision of the society that could offer the sociologists. The two answers until now collapsed the socialism, before which actions are requested to us, are post modernism and the new era. Resumen. El Profesor Alonso Tobón comenta en su ponencia "Los actuales desafíos de la Sociología", el balance presentado por la profesora Alba Lucía Serna acerca de la Sociología en Medellín y los comentarios de los profesores María Teresa Uribe, Javier Galeano, Edgar Ramírez y Juan María Ramírez, que apuntan a un diagnóstico de crisis en la sociología y a un pronóstico reservado, teniendo en cuenta la falta de perspectivas, la ausencia de diálogo y la falta de comunidades académicas. El plantea que si .queremos aceptar el reto de hacer avanzar la Sociología hay que volver a la Sociología científica. Argumenta que es positivo el aumento de la matrícula, y la alta oferta de egresados; muestra que la situación es optimista. Tobón plantea cuatro desafíos de la sociología actual: Agremiación o colegios profesionales: sugiere la creación de formas de asociaciones, instituciones académicas o colegios que monopolicen el saber y el desempeño profesional. El ejercicio de la Profesión, ocupación, empleo: la sociología se debate por tanto en ser una profesión o una ocupación. El refugio para la profesión ha sido la docencia universitaria. Ciencia o humanidades: métodos cualitativos o cuantitativos La visión de la sociedad que podrían ofrecer los sociólogos. Las dos respuestas hasta ahora, derrumbado el socialismo, ante las cuales se nos piden acciones, son el post modernismo y la nueva era.